PENGEMBANGAN LEMBAR AKTIVITAS SISWA BERBASIS MODEL DISCOVERY LEARNING PADA MATERI ARITMATIKA - Tommy Tanu Wijaya; Solikhotur Rofiah; Nia Wahyu Damayanti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Student Activity Sheet is one of the learning materials that is often used in mathematics lessons in Indonesia. This study aims to develop student activity with a discovery learning model. The method used in this research is development research which refers to the development stage by Plomp and Nieveen which consists of three stages, namely, initial investigation, prototyping stage, and assessment stage. However, researchers conducted research only up to the step of making prototypes and testing the validation of learning materials. At the initial investigation stage, the data on difficulties in understanding the concepts of students and in the material for the sequence and series determining the nth term were analyzed. At the prototype stage, the researcher developed the student activity sheet which was carried out by adopting the steps of the discovery learning method. The results of developing a valid learning material are useful for providing examples of student activity sheet with a discovery learning model. The results of the validation of the Student Activity Sheet Implementation Plan obtained that the final criteria were very good and were in the very valid category, which means that the student activity sheet is suitable for use in learning.